A Leapfrog To Financial Inclusion: The Role of Mobile Money and Digital Financial Services on Financial Inclusion and Its Implications for Other Developing Economies - Banda-Nyirenda, Eluphy; Seleka, Gaone Geoffrey; Mwanza, Charity Chitalu; Phiri, Thomas (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: This study offers a thorough empirical analysis of Botswana's current financial inclusion situation, aiming to measure and evaluate the direct impact of mobile money and digital financial services offered by mobile network operators (MNOs) and commercial banks on the financial behaviour, access to financial services, and overall financial inclusion status of the unbanked population in Botswana. These study objectives are expected to have possible implications for other developing nations or economies. Design/methodology/approach: The study adopted a pragmatic philosophy, combining positivist (qualitative) and interpretivist (qualitative) philosophies, and a mixed-methods approach to explore the experiences of the unbanked population in Gaborone, Botswana. Findings: Mobile money and digital financial services have significantly impacted the financial behaviour of the unbanked population in Botswana, providing an accessible and affordable financial platform. Additionally, there are still areas that require further research and intervention to ensure that these gains are sustainable and inclusive. This study contributes to academic knowledge in business studies and financial technologies, providing practical guidance to MNOs, regulators, banks, and policymakers, and offering marketing insights. Paper type: Research paper.